(3MOjK GdeUGaMI heSdSdGJ CHj GdMSf GdbQGaj Ydi CHj ESMGb EHQGgje Hf Gdabjg fhQ GdOjf Ydi GdHjVGhis - (3eMeO Hf jYbhH Hf eMeO, eLO GdOjf GdajQhRGHGOj,J (B817 (3g` s
(3ChdgG (B:s
(3bQCJ Ydi GdTjN CHj ESMb GdHjVGhi SeYJ Ydi GdbGVi GdYdGeI eLO GdOjf CHj GdWGgQ eMeO jYbhH GdajQhRCHGOi s
(3BNQgG (B:s
(3eJi fGeJ GdYjhf hYjfi SjOi dG JfGe SHMGf GdOGFe GdbGFe SHMGf ef Ndb GdEUHGM hcGf QShd Gddg Udi Gddg Ydgj hSde jHjJg eYg ai GdHjJ s
(3GdfSNI HgG MhGTs
(3HgG JQGLe GdYdeGA GdMOjK hCNP HYVge Yf HYV hNGUI ai GdYUhQ GdeJCNQIs
(3HgG fXGe GdJYbjHIs
(3YdjgG NW EHQGgje Hf Ydi Hf eMeO Hf OGhhO GdReRei Gdeci hajgG eSdSdGJ cKjQI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B147s
Keywords: (3GdMOjK h GdeUWdMs